ANALISIS GAYA KEPEMIMPINAN BERDASARKAN GENDER PADA PERUSAHAAN PENERBANGAN DI JAKARTA - Dita Oki Berliyanti; Netalia Emilisa; Beta oki Baliartati (Universitas Trisakti, 2004)
These days working world is dominated by woman become a trend. So there's a change that more woman will be a leader. This fact will impact to the behavior and work system of employees. The study aims to prove that there are basic differences between man and woman in leadership which known in theory as transactional leadership and transformational leadership. The result of this study can give suggertion to employee in order to anticipate the leadership style of the leader and make adjustment for each other, The result is shows there are differences between man and woman leadership style, where man leadership style is more transactional and woman leadership style is more transformational.